In search of divine reality : science as a source of inspiration - Schäfer, Lothar, 1939- (University of Arkansas Press, 1997)
"In this remarkable treatise, Professor Schafer shares his conclusions from a lifelong search for evidence - from quantum science - of the existence of a transcendent part of physical reality, combining disciplinary thought from science, philosophy, and religion, including ethics, to address the educated generalist and layman with a profound look at existence." "Braving controversy, Professor Schafer concludes that the discovery of the phenomena of quantum mechanics has established a new covenant - between the human mind and the mind-like background of the universe - one that provides a home again to the homeless and meaning to seemingly pointless life. In this new understanding of the world, the universe must be assumed to have a moral as well as a physical order, and facts and values derive, again, from a single source."--Jacket